Volume 2C: Turbomachinery 2018
DOI: 10.1115/gt2018-77125
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Prediction of Loss Using High Fidelity Methods

Abstract: Further improvements in aero-engine efficiencies require accurate prediction of flow physics and incurred loss. Currently, the computational requirements for capturing these are not known leading to inconsistent loss predictions even for scale-resolving simulations depending on the chosen convergence criteria. This work investigates two aspects of loss generation using high-fidelity simulation. In the first case study we look at the effect of numerical resolution on capturing viscous dissipation by simulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Second, the entropy transport equation was used to determine the unresolved dissipation. Two sub-volumes of data are extracted from the tip gap and an entropy budget calculation conducted in the same manner as [19]. The subvolumes are shown in Fig.…”
Section: Mesh Resolutionmentioning
confidence: 99%
“…Second, the entropy transport equation was used to determine the unresolved dissipation. Two sub-volumes of data are extracted from the tip gap and an entropy budget calculation conducted in the same manner as [19]. The subvolumes are shown in Fig.…”
Section: Mesh Resolutionmentioning
confidence: 99%
“…To establish guidelines for what simulation fidelity, in terms of grid resolution and order-of-accuracy, is required to correctly capture entropy losses, Przytarski & Wheeler [109] established that the entropy generation rate based on the entropy flux could be used as a proxy for loss. Using a Taylor-Green vortex problem to represent fully turbulent flow, it was shown that a grid resolution with spacing of 4 and 2 times the Kolmogorov scale for 8th-order and 4th-order accurate schemes, respectively, was required for an accurate prediction of the entropy loss.…”
Section: Entropy Based Simulation Quality Assessmentmentioning
confidence: 99%
“…Influence of different numerical schemes of divergence part:Both KEP(kinetic energy preserving) and CR(Chain-Rule) are used for the calculation of divergence part of the flux reconstruction discretization as Eq(7). The computational speed of CR is slightly faster than KEP while the result is nearly the same fromFig.…”
mentioning
confidence: 99%